Digital Governance and Citizen Trust: Evaluating the Impact of e-Service Delivery on Public Satisfaction in Bangladesh’s Upazila Administration - Md. Ruhul Amin (Journal of Interdisciplinary Social Sciences and Humanities, 2026)
Digitization of governance at the level of Upazila (sub-district) in Bangladesh has brought significant changes, which have changed the way individuals access the services of the government. These developments have not benefited all people equally especially in areas that are remote and rural. This research paper identifies some achievements and ongoing challenges since it explores the relationship between e-service delivery and its impact on the level of trust and satisfaction among the people in Upazila administrations. The study is a synthesis of the findings of government reports, official publications, and 202025 research papers relying on the mixed-method approach and secondary research. Although qualitative data can shed some light on the experiences, attitudes, and trust in the local government, quantitative analyses assess trends in the satisfaction of the population and service provision. The research reports that the digital services such as online registering of births, property records, and processing of business licenses have significantly enhanced convenience, accountability and transparency as well as public trust. Government services are perceived by people as more reliable save money and time and less bureaucratic hurdles. Barriers still exist, but poor internet connectivity, the lack of digital literacy, inconsistent service quality, and data security concerns. The report recommends the increased connection, promotion of digital literacy, ensuring the safety of datas managed, standardization of the quality of services everywhere within Upazila, and integration of the citizen feedback into the resolution of these issues. As such, this research reveals that whereas technology helps in the promotion of efficiency, inclusive access, comprehension trust are required to bring some real transformation in the provision of public services. It is to say that Digital Bangladesh still needs to be a person-centered journey but not entirely a system-based one.